A community of clones: Snow algae are diverse communities of spatially structured clones - Brown, Shawn Paul; Ungerer, Mark C.; Jumpponen, Ari (My University, 2016)
Premise of research. Snow algae are cosmopolitan and often colonize late-season snowpacks. These snow algae do not occur in isolation; rather, visible algal blooms consist of multispecies communities. Although several of these common snow algae have been characterized taxonomically, their inter- and intraspecific diversity remains unknown. Further, the phylogeographic and biogeographic structuring of snow algal species is poorly understood. Methodology. Algal communities were censused by sequencing the variable internal transcribed spacer 2 locus using Illumina MiSeq. We further analyzed two of the most common and abundant algal operational taxonomic units (OTUs) for biogeographic haplotype diversity. Pivotal results. Our data show that the communities are diverse and taxonomically broad (orders: Chlamydomonadales [74% of OTUs], Microthamniales [20% OTUs], and Chlorellales [6% OTUs]). We demonstrate that the two most common species (best nucleotide basic local alignment search tool match to Coenochloris sp. and Chlamydomonas sp.) have distinct haplotype distributions locally and regionally. Each sampled algal colony was dominated by one and only one haplotype, with negligible intraspecific haplotype diversity. Conclusions. Our results suggest that snow algae are communities of clones within a discrete patch yet are heterogeneous across the landscape. Thus, these communities are likely structured via strong priority effects, intense kin competition, and dispersal limitations. © 2016 by The University of Chicago. All rights reserved.
Citation: Brown, S. P., Ungerer, M. C., & Jumpponen, A. (2016). A community of clones: Snow algae are diverse communities of spatially structured clones. International Journal of Plant Sciences, 177(5), 432-439. doi:10.1086/686019
Keywords: Biogeography; Clonal; Haplotype; Illumina Miseq; Snow Algae; Algae